Calidad Sensorial de Totopos de Pozol Adicionados con Chaya (Cnidoscolus aconitifolius) y Hierba Mora (Solanum nigrum) - Guillermo-Moreno, Rafael; Durán-Mendoza, Temani; González-Cortés, Nicolás; Jiménez-Vera, Román (European Scientific Journal, ESJ, 2019)
La tortilla de maíz constituye uno de los pilares más importantes de la alimentación en México. Los totopos son porciones de tortilla fritas o tostadas, poseen una textura crujiente y suelen consumirse acompañando otras comidas. El objetivo de este trabajo fue evaluar el nivel de agrado de totopos de pozol adicionados con hojas de chaya (Cnidoscolus aconitifolius) y hierba mora (Solanum nigrum). La evaluación sensorial fue realizada con 50 jueces no entrenados. Se encontró que el nivel de agrado del totopo natural, fue de 4.9 ± 1.4 en una escala hedónica de siete puntos; este valor corresponde al rango “ni me gusta ni me disgusta”. Los totopos experimentales obtuvieron una mayor aceptación: los adicionados con chaya, 5.7 ± 1.2 y los suplementados con hierba mora, 5.7 ± 1.0, calificados como “me gusta” en la escala hedónica. Al aplicar la prueba de comparación de medias DMS (P The corn tortilla is one of the most important pillars of power in Mexico. The tortilla chips are pieces of fried tortilla or toasted. They have a crunchy texture and are usually eaten with other foods. This paper focuses on assessing the level of liking of pozol tortilla chips added with chaya leaves (Cnidoscolus aconitifolius) and black nightshade (Solanum nigrum). Sensory evaluation was performed with 50 not-trained judges. We found that the level of liking of the natural tortilla chips was 4.9 ± 1.4 on a seven-point hedonic scale. This value corresponds to the range "I like or I dislike". The experimental tortilla chips obtained greater acceptance: the add-on with chaya 5.7 ± 1.2 and the supplemented with black nightshade, 5.7 ± 1.0, qualified as a "like" on the hedonic scale. By applying the average DMS test (P < 0.05), it was found that there is a significant difference between the experimental chips and reference. The addition of black nightshade and chaya improved the acceptance of pozol tortilla chips. Hence, it is possible to improve the quality of the snacks with the addition of nutritious vegetables. In the development of new products, it is important to consider the sensory quality and ensure a good level of satisfaction among consumers. This is because consumers are those who determine the acceptance or rejection of a product.